Combining Ability Estimates and Heterosis for Yield and Fiber Quality of Cotton in Line x Tester Design - Cetin KARADEMIR; Emine KARADEMIR; Remzi EKINCI; Oktay GENCER (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2009)
The objective of this study was to facilitate the selection in cotton breeding program and estimate the general combining ability (GCA) of the parents and specific combining ability (SCA) of hybrids considered for the development of high yielding and better fiber quality in early generations. The study was carried out at the Southeastern Anatolia Agricultural Research Institute during 2006 and 2007 cotton growing season. Seven cotton lines (which are known as high quality) and three testers (which are known as well adapted and high yielding) were crossed in a line x tester mating design in 2006. Ten genotypes and 21 F1 hybrids were planted in the randomized complete block design with three replications at the same experimental area in 2007. The variance due to GCA and SCA were highly significant for all the traits studied. This indicated that both additive and non-additive gene effects were responsible for the investigated characters. From the trial it was found that in the population, fiber length, fiber fineness and fiber elongation were influenced by additive gene effects while seed cotton yield, fiber yield, ginning percentage, fiber strength and fiber uniformity were influenced by non-additive gene effects. Among the parents FiberMax 832, Teks, Stoneville 453 and Maraş 92 for seed cotton yield and fiber yield; Aşkabat 71 and Giza 45 for fiber length and fiber strength; Aşkabat 71 for fiber fineness and fiber uniformity were detected with higher general combining ability. Most of the parents except Aşkabat 71, Giza 45 and Maraş 92 exhibited GCA for ginning percentage. SCA was significant for FiberMax 832 x Stoneville 453, Tam 94 L 25 x Maraş 92 and Teks x Stoneville 453 hybrid combinations for yield with acceptable fiber quality.